The Comparative Study on the Behavior of the Speed Reducer With Worm Face Gear With Modified Geometry. (2016) - Boantă, Claudiu-Ioan; Boloş, Vasile
Abstract: The paper highlights the findings of the research on the thermal limits of a speed reducer equipped with a worm face gear with modified geometry made of hardened steel 42MoCr11x by nitrocarburizing (cylindrical worm) and improved steel OLC 45 (worm face wheel). This type of gear is a worm face gear variant where of the worm flanks are executed with equal pressure angles to simplify the geometry tools and execution technology. The paper made a comparison with thermal limit values for other types of worm face gears obtained by the authors.